PRODUKSI VFA,NH3, DAN PROTEIN TOTAL SECARA IN VITRO PADA FODDER JAGUNG HIDROPONIK DENGAN MEDIA PERENDAMAN DAN PENGGUNAAN DOSIS PUPUK YANG BERBEDA (The Production Of Vfa, NH3 And Total Proteins In Vitro Hydroponic Corn Fodder With Submersion Medium And Usage Of Different Fertilizer Doses) - A. I. Izzatullah; . Sutrisno; L. K. Nuswantara (Fakultas Peternakan, Universitas Hasanuddin, Makassar, 2018)
This study aims to identify the interaction between submersion medium and fertilizer dosage level on the production of VFA, NH3 and total protein in hydroponic fodder maize. Research design used 2 x 3 factorial with 3 replication. The first factor includes M0 (without soaked H2SO4) and M1 (soaking H2SO4). The second factor includes N0 (0 gram), N1 (0,5 gram) and N2 (1 gram) of fertilizer/liter water. The method used is soaking of corn seeds, planting hydroponic fodder maize, fertilization done on day 3 and 13, harvesting done on day 15, drying and flouring, and analyzed in vitro to determine the production of VFA, NH3 and total protein. Research shows there are interaction between submersion medium and fertilizer dosage level on VFA production of hydroponic fodder maize, while there is no interaction on the production of NH3 and total protein. There is a significant effect on different fertilizer dosage levels on the production of VFA and NH3, but no significant effect on total protein production. There is no significant effect on the submersion media on the production of VFA, NH3 and total protein.